Stigma-Stop: A Serious Game against the Stigma toward Mental Health in Educational Settings - Cangas, Adolfo J.; Navarro, Noelia; Parra, José M. A.; Ojeda, Juan J.; Cangas, Diego; Piedra, Jose A.; Gallego, Jose (Frontiers in Psychology, 2017)
This paper presents the results from the application of a serious game called Stigma-Stop among a group of high school students with the aim of reducing the stigma towards mental illnesses. The video game features characters with various mental disorders (schizophrenia, depression, bipolar disorder, and panic disorder with agoraphobia) and provides information about these problems. Additionally, the game asks players about whether they have ever felt the same as the characters, if they believe the characters are psychologically well, and if they think they could help these individuals. Similarly, a variety of reactions are provided for players to choose from when they encounter the characters with these problems. A total of 552 students between the ages of 14 and 18 participated in the study, and they were randomly assigned to either the experimental group, which used Stigma-Stop, or the control group, which utilized a video game completely unrelated to mental health. Both video games were used for similar lengths of time. Following the application of Stigma-Stop, a statistically significant decrease was obtained in levels of stigma towards schizophrenia, both in terms of stereotypes and, to a greater extent, its potential dangerousness. However, this was not the case in the control group. Results thus demonstrate the video game’s usefulness towards eradicating erroneous notions about serious mental disorders like schizophrenia.